Monoclonal Antibody Functionalized, and L-lysine α-Oxidase Loaded PEGylated-Chitosan Nanoparticle for HER2/Neu Targeted Breast Cancer Therapy - Kandasamy Saravanakumar; Anbazhagan Sathiyaseelan; Soyoung Park; Song-Rae Kim; Veeraraghavan Vishnu Priya; Myeong-Hyeon Wang (MDPI AG, 2022)
Herein, we designed a nanocarrier to deliver the LO specifically to HER2+ breast cancer (BC) cells, where functionalization of mAb (anti-HER2+) with PEGylated chitosan enabled it to target the HER2+ BC cells. Taking advantage of overexpression of HER2+ in cancer cells, our nanocarrier (CS-LO-PEG-HER NPs) exhibited promising potency and selectivity against HER2+ BC cells (BT474). The CS-LO-PEG-HER NPs demonstrated the cytotoxicity in BT474 cells by promoting reactive oxygen species, mitochondrial membrane potential loss, and nucleus damage. The biocompatibility of CS-LO-PEG-HER NPs was evidenced by the hemolysis assay and H & E staining of major organs. The CS-LO-PEG-HER NPs showed anticancer potency against the BT474-xenograft tumor-bearing mice, as evident by the reduction of tumor size and cell density. These results indicate that CS-LO-PEG-HER NPs are biocompatible with mice while inhibiting tumor growth through alter the oxidative stress. Overall, this work provides a promising approach for the delivery of LO for good therapeutic effect in combination with mAb.